The relationship between leg muscle mass and leg muscle explosive power on vertical jump height in basketball athletes - Shurdi, Nazilatus; Fithroni, Hijrin; Wismanadi, Himawan; Fikri, Muhammad Dzul (Sriwijaya Journal of Sport, 2026)
Research Problems: Basketball is a high-intensity sport that demands physical endurance, including strength, agility, endurance, speed, flexibility, balance, and explosive muscle power, while combining technical skills, tactical intelligence, and mental toughness. Increased leg muscle mass is directly proportional to strength and explosive power, which play an important role in jumping and shooting success. Research Objectives: This study aims to examine the relationship between leg muscle mass and leg muscle explosive power with jump height in basketball athletes, and the results can serve as a reference for coaches in designing more varied and effective training programs to improve overall team performance. Methods: This study uses a quantitative approach and correlation tests on 21 UNESA student league athletes, comprising 11 men and 10 women. Leg muscle mass instruments were taken using the Onpoint tool, while data on leg muscle explosive power and jump height were obtained using the Forcedecks tool. Results: The results of this study concluded that the three variables showed significant results, with data on left leg muscle mass (r=0.728; p=0.001) and right leg muscle mass (r=0.712; p=0.001) with jump height and data on leg muscle explosive power with jump height (r=0.813; p=0.001). Conclusion: these findings prove that increasing leg muscle mass and leg muscle explosive power contribute significantly to the vertical jump ability of basketball athletes, with leg muscle explosive power being the dominant factor in determining jump height.